Caste and Punishment : The Legacy of Caste Culture in Norm Enforcement - Hoff, Karla; Kshetramade, Mayuresh; Fehr, Ernst (2012)
Well-functioning groups enforce social norms that restrain opportunism, but the social structure of a society may encourage or inhibit norm enforcement. This paper studies how the exogenous assignment to different positions in an extreme social hierarchy - the caste system - affects individuals' willingness to punish violations of a cooperation norm. Although the analysis controls for individual wealth, education, and political participation, low-caste individuals exhibit a much lower willingness to punish norm violations that hurt members of their own caste, suggesting a cultural difference across caste status in the concern for members of one s own community. The lower willingness to punish may inhibit the low caste s ability to sustain collective action and so may contribute to its economic vulnerability.